2020
DOI: 10.1590/0103-11042020e208
|View full text |Cite
|
Sign up to set email alerts
|

A utilização de instrumentos globais para a avaliação da resiliência a desastres na saúde

Abstract: RESUMO Com o aumento dos eventos extremos nas cidades, os gestores locais precisam tomar medidas que minimizem os impactos negativos resultantes dos desastres. A área de saúde é uma das que mais possuem interferências, com o crescimento do número de afetados, feridos, mortos, além dos problemas psicológicos e de qualidade de vida após os eventos. O objetivo da presente pesquisa foi analisar a resiliência a desastres na saúde por meio do instrumento global Disaster Resilience Scorecard for Cities. O Scorecard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This study found that from 51,184 disaster events that occurred in Brazil from 2013 to 2021, 50,481 (98.62%) were natural disasters, mostly climatological ones (23,452). Regarding human damage, the natural biological disasters led to the highest number of victims (321,111 deaths, 208,720 injuries, and 7,041,099 sick individuals).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This study found that from 51,184 disaster events that occurred in Brazil from 2013 to 2021, 50,481 (98.62%) were natural disasters, mostly climatological ones (23,452). Regarding human damage, the natural biological disasters led to the highest number of victims (321,111 deaths, 208,720 injuries, and 7,041,099 sick individuals).…”
Section: Discussionmentioning
confidence: 75%
“…For example, the COVID-19 pandemic is considered a biological disaster and overwhelmed the public health system, compromising health assistance directed to other health problems. Thus, it is essential to prepare health professionals to provide adequate healthcare to the population and overcome the challenges posed by critical emergency scenarios 23,24 .…”
Section: Discussionmentioning
confidence: 99%